YODA Kinase Controls a Novel Immune Pathway of Tomato Conferring Enhanced Disease Resistance to the Bacterium Pseudomonas syringae - Téllez, Julio; Muñoz-Barrios, Antonio; Sopeña-Torres, Sara; Martín-Forero, Amanda F.; Ortega, Alfonso; Pérez, Rosa; Sanz, Yolanda; Borja, Marisé; de Marcos, Alberto; Nicolas, Michael; Jahrmann, Torben; Mena, Montaña; et al. (Frontiers in Plant Science, 2020)
Mitogen-activated protein kinases (MAPK) play pivotal roles transducing developmental cues and environmental signals into cellular responses through pathways initiated by MAPK kinase kinases (MAP3K). AtYODA is a MAP3K of Arabidopsis thaliana that controls stomatal development and non-canonical immune responses. Arabidopsis plants overexpressing a constitutively active YODA protein (AtCA-YDA) show broad-spectrum disease resistance and constitutive expression of defensive genes. We tested YDA function in crops immunity, by heterologously overexpressing AtCA-YDA in Solanum lycopersicum. We found that these tomato AtCA-YDA plants do not show developmental phenotypes and fitness alterations, except a reduction in stomatal index, as reported in Arabidopsis AtCA-YDA plants. Notably, AtCA-YDA tomato plants show enhanced resistance to the bacterial pathogen Pseudomonas syringae pv. tomato DC3000 and constitutive up-regulation of defence-associated genes, corroborating the functionality of YDA in tomato immunity. This function was further supported by generating CRISPR/Cas9-edited tomato mutants impaired in the closest orthologues of AtYDA (Solyc08g081210 (SlYDA1) and Solyc03g025360 (SlYDA2)). Slyda1 and Slyda2 mutants are highly susceptible to P. syringae pv. tomato DC3000 in comparison to wild-type plants but only Slyda2 shows altered stomatal index. These results indicate that tomato orthologues have specialized functions and support that YDA also regulates immune responses in tomato and may be a trait for breeding disease resistance.